The priming potential of environmentally weathered pyrogenic carbon during land-use transition to biomass crop production - McClean, Gary J.; Meredith, Will; Cross, Andrew; Heal, Kate V.; Bending, Gary D.; Sohi, Saran P. (Wiley, 2016)
Since land-use change (LUC) to lignocellulosic biomass crops often causes a loss of soil organic carbon (SOC), at least in the short term, this study investigated the potential for pyrogenic carbon (PyC) to ameliorate this effect. Although negative priming has been observed in many studies, most of these are long-term incubation experiments which do not account for the interactions between environmentally weathered PyC and native SOC. Here, the aim was to assess the impact of environmentally weathered PyC on native SOC mineralization at different time points in LUC from arable crops to short rotation coppice (SRC) willow. At eight SRC willow plantations in England, with ages of 3–22 years, soil amended 18–22 months previously with PyC was compared with unamended control soil. Cumulative CO2 flux was measured weekly from incubated soil at 0–5 cm depth, and soil-surface CO2 flux was also measured in the field. For the incubated soil, cumulative CO2 flux was significantly higher from soil containing weathered PyC than the control soil for seven of the eight sites. Across all sites, the mean cumulative CO2 flux was 21% higher from soil incubated with weathered PyC than the control soil. These results indicate the potential for positive priming in the surface 5 cm of soil independent of changes in soil properties following LUC to SRC willow production. However, no net effect on CO2 flux was observed in the field, suggesting this increase in CO2 is offset by a contrasting PyC-induced effect at a different soil depth or that different effects were observed under laboratory and field conditions. Although the mechanisms for these contrasting effects remain unclear, results presented here suggest that PyC does not reduce LUC-induced SOC losses through negative priming, at least for this PyC type and application rate.